IMPLEMENTATION of SDGs – 4 THROUGH DIGITIZATION OF EDUCATION AT SANGGAR BIMBINGAN KUALA LANGAT, SELANGOR, MALAYSIA - Churiyah, Madziatul; Agustina, Yuli; Pratikto, Heri; Arief, Mohammad; Abdilah, Eka Novianti; Camelia N. C., Inneke; Al Azhar, M. Habib; Albar Bari'na, Moch. Yusufa (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Lecturers from Universitas Negeri Malang conducted Overseas Partnership Service activities at Sanggar Bimbingan Kuala Langat, Selangor, Malaysia. This service activity aims to enhance the quality of teaching and the understanding of both teachers and parents of students in the guidance studio, aligning with SDGs Goal 4, which is "Quality Education." The need for this service activity arises from the teachers' lack of understanding regarding learning media and models applicable in the classroom. Several specific activities were carried out, including a workshop titled "Enhancing Learning Quality and Teacher-Parent Understanding at Sanggar Belajar Kuala Langat, Selangor, Malaysia, Using the Flipped Classroom Learning Model." These activities also included a video tutorial demonstrating "How to Utilize Google Classroom as a supportive tool for the Flipped Classroom learning model" and assistance in setting up Google Classroom accounts and using the application. Through these activities, it was observed that both teachers and parents gained a better understanding of the flipped classroom learning model and the use of Google Classroom as a teaching tool. Consequently, it is anticipated that the learning quality at Sanggar Bimbingan Kuala Langat will see improvement.